2022
DOI: 10.21203/rs.3.rs-1658265/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intracameral air bubble tamponade in routine cataract surgery

Abstract: Purpose: To evaluate the efficiency, safety, and postoperative outcomes of intracameral air bubble tamponade (IABT) following phacoemulsification cataract surgery.Methods: We retrospectively reviewed all patients receiving phacoemulsification from 2016 to 2017 performed by one ophthalmic surgeon HCC. Incisions were closed with either non-IABT or IABT. In IABT group, air bubble was injected into the anterior chamber until its size reached 80% of the corneal diameter. Operation time, visual acuity (VA), and intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Although this disease afflicts humans for years, the clinical drugs currently use for urate-lowering therapies are limited and most of them are considered to be associated with various adverse effects (13,15). Probiotic treatment might be a promising strategy for anti-hyperuricemia intervention (22)(23)(24)(25). In this study, we revealed that LR1155 and LF2644 isolated from Chinese traditional fermented dairy food exhibited an antihyperuricemia effect, and the underlying mechanism for each strain was testified.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although this disease afflicts humans for years, the clinical drugs currently use for urate-lowering therapies are limited and most of them are considered to be associated with various adverse effects (13,15). Probiotic treatment might be a promising strategy for anti-hyperuricemia intervention (22)(23)(24)(25). In this study, we revealed that LR1155 and LF2644 isolated from Chinese traditional fermented dairy food exhibited an antihyperuricemia effect, and the underlying mechanism for each strain was testified.…”
Section: Discussionmentioning
confidence: 89%
“…Gut microbiota dysbiosis caused by hyperuricemia was regulated by supplementation of L.brevis DM9218 or L. fermentum JL-3 (23,24). Moreover, microbial fermented extracts of Lactobacillus were reported to prevent the UA elevation by inhibiting the XOD activity (25). However, whether the LAB strains may play a role in the aspect of UA excretion effects has not been clarified.…”
Section: Introductionmentioning
confidence: 99%